221k views
4 votes
Which is the simplified form of the expression ((p squared) (q Superscript 5 Baseline)) Superscript negative 4 Baseline times ((p Superscript negative 4 Baseline) (q Superscript 5 Baseline)) Superscript negative 2? HURRY PLEASE ANSWER THIS!!!

2 Answers

2 votes

Answer:

q^30 is not the answer i get it wrong idk what the answer is yet

Explanation:

User SamBremner
by
4.5k points
6 votes

Answer:


q^(-30)

Explanation:

Given the expression:


((p^2) (q ^5)) ^(-4) X ((p ^(-4)) (q^5)) ^(-2)

First, we open the outer brackets


=(p^(2X-4)) (q ^(5X-4))X (p ^(-4X-2)) (q^(5X-2))\\\\=(p^(-8)) (q ^(-20))X (p ^(8)) (q^(-10))\\\\$Next, we can collect like terms\\\\=p^(-8)Xp ^(8)Xq ^(-20)Xq ^(-10)\\\\$Applying addition law of indices\\\\=p^(-8+8)Xq^(-20+(-10))\\\\=p^0 X q^(-30)\\\\=1 X q^(-30)\\\\=q^(-30)

Therefore:


((p^2) (q ^5)) ^(-4) X ((p ^(-4)) (q^5)) ^(-2)=q^{-30

User Vikram Parimi
by
4.9k points